Exercise training improves exercise capacity despite persistent muscle mitochondrial dysfunction in the taz shRNA mouse model of human Barth Syndrome - Claiborne, Michael Scott, author; Chicco, Adam J., advisor; Hamilton, Karyn, committee member; Miller, Benjamin, committee member; Tamkun, Michael, committee member (Colorado State University. Libraries, 2013)
Barth Syndrome is a mitochondrial disease associated with exercise intolerance and cardioskeletal myopathy resulting from mutations in the tafazzin (taz) gene. The present study characterized skeletal muscle mitochondrial function and exercise capacity of a taz shRNA mouse model of Barth Syndrome (90% taz-deficient), and examined the effect of exercise training on these parameters. Mitochondrial respiratory function was assessed, in mitochondria freshly isolated from hindlimb muscles, using an Oroboros O2K respirometer with pyruvate + malate as substrates, oligomycin as an ATP synthase inhibitor, and carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP) to establish maximal activity. A pre-training GXT revealed profound exercise intolerance, which corresponded to reduced respiratory capacity, citrate synthase (CS) and ETC complex 1 protein content of muscle mitochondria in the taz vs. age-matched wild-type (WT) mice. Based on the pre-training GXT, exercise training was conducted at 12-17 m/min, 0% grade for 60 min/d, 5d/wk, for 4 wks. Exercise training elicited a 99% increase in GXT run time in the taz mice (P < 0.01 vs. pre-training), but failed to increase times to those of sedentary WT mice. Training significantly decreased state 3 respiratory capacity of muscle mitochondria from exercised mice (wild type sedentary (WTS): 4992.59 ± 371.35, wild type exercised (WTX): 3779.60 ± 561.43, taz sedentary (TazS): 2978.50 ± 383.53, TazS: 1827.55 ± 525.17 (pmolO2/(s*mg), P = 0.02, Sed. vs. Ex.), and significantly decreased mitochondrial CS activity in taz mice (WTS: 4.48 ± 0.51, WTX: 3.87 ± 0.69, TazS: 3.21 ± 0.54, taz exercised (TazX): 1.63 ± 0.69 (relative absorbance/gram of protein) (RU/g), P = 0.01). Training also tended to reduce mitochondrial lactate dehydrogenase (LDH) and monocarboxylate transporter 1 (MCT1) activities, MnSOD content, and 4-hydroxnonenal-protein adducts (index of oxidative stress), but tended to increase mitochondrial UCP3 in exercised WT and taz mice. Interestingly, training significantly increased muscle levels of CS (WTS: 1.491 ± 0.112, WTX: 1.792 ± 0.143, TazS: 1.325 ± 0.108, TazX: 1.550 ± 0.143 (RU/g), P = 0.05 Sed. v. Ex.), suggesting increased muscle mitochondrial content with training. This study indicates that exercise training improves functional capacity of taz deficient mice and induces selective mitochondrial protein remodeling during mitochondrial biogenesis that perhaps mitigates oxidative stress while adapting to increased metabolic demand.
Keywords: skeletal muscle; mitochondria; tafazzin; Barth Syndrome; exercise